Anion diffusion processes in O- and N-mayenite investigated by neutron powder diffraction - Boysen, Hans; Kaiser-Bischoff, Ines; Lerch, Martin (Diffusion Fundamentals, 2008)
The crystal structure of mayenite (ideal composition: Ca12Al14O33) consists of a (disordered) calcium-aluminate framework comprising 32 of the 33 oxygen anions. It contains large open cages, 1/6 of them being filled randomly by the remaining “free” oxygen which is available for diffusion and very high ionic conductivities. This extraframework oxygen could be substituted by nitrogen, opening up possibilities for a pure nitrogen ionic conductor. From high temperature neutron powder diffraction experiments, data analysis employing difference Fourier methods and anharmonic Debye-Waller factors and comparing pure O-mayenite with partly exchanged N/O-mayenite it is concluded that oxygen diffusion proceeds via jump-like processes, intimately coupled to relaxations of Ca and involving exchange of the “free” oxygen with framework oxygen, while nitrogen diffusion appears to proceed via an interstitial process.